Strengthening Artistic Competence Through Angklung Performance in the Merdeka Curriculum: A Qualitative Study of PGSD Students - Firtikasari, Melsya; Soeteja, Zakarias S; Narawati , Tati; Latifah, Diah; Nurihsan, Juntika; Jupri , Al Jupri (WAHANA, 2026)
The implementation of the Merdeka Curriculum emphasizes student-centered learning through authentic and meaningful experiences that support competency and character development. One learning approach aligned with these objectives is arts-based project learning through angklung performance. This study aimed to explore how angklung performance contributes to strengthening the artistic competence of Elementary School Teacher Education (PGSD) students within the context of the Merdeka Curriculum. A qualitative case study design was employed involving PGSD students at Nusa Putra University, Sukabumi, who participated in a series of angklung performance activities as part of project-based learning. Data were collected through participant observation, semi-structured interviews, reflective documentation, and field notes. The data were analyzed using thematic analysis supported by source triangulation and member checking to ensure trustworthiness. The findings revealed four major themes: improvement of musical and artistic skills, enhancement of collaborative learning and communication, strengthening of cultural awareness and appreciation of local heritage, and development of responsibility, discipline, and self-confidence. However, participants also encountered challenges related to limited musical backgrounds and restricted rehearsal time. The study demonstrates that angklung performance serves as an effective culturally responsive learning strategy that supports artistic competence development while promoting the values of the Pancasila Student Profile. These findings provide practical implications for integrating traditional arts into teacher education programs within the Merdeka Curriculum framework